Pemeriksaan Odontologi Forensik pada Identifikasi Korban Masal di Medan - Amri Amir (Faculty of Dentistry, Universitas Indonesia, 2015)
Forensic odontology (FO) has played an important role in the process of identification of unknown victims. This has help doctor dentist and forensic expert to a great extents. The process of identification of 2 plane crash victims of Garuda DC 10 in 1987 and Garuda Air-Bus in 1995, and 41 murder victims executed by Dukun AS after exhumationed are discussed here. The need of a well trained dentists in the field of FO is imperative as a companion of doctors and forensic experts in the process of examining cases of unknown origin criminal cases and mass disasters victims. It is expected in the future that the demand of Forensic Odontologist is a must in several health service centers in Indonesia.